2023
DOI: 10.22159/ijap.2023.v15s1.06
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Multicomponent Crystal of Trimethoprim and Mandelic Acid by Solvent Drop Grinding Method

Abstract: Objective: To increase the solubility of trimethoprim by forming multicomponent crystals using mandelic acid as a coformer. Methods: Multicomponent crystals of trimethoprim and mandelic acid were prepared at a ratio of 1:1 mol by the Solvent Drop Grinding (SDG) method. Solid state characterization was carried out using Differential Scanning Calorimetry (DSC), Powder X-ray Diffraction (PXRD), Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscope (SEM), and polarized microscope. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…1. the changes in the crystal lattice that occur due to the solid-state interaction between trimethoprim and mandelic acid molecules [13]. The type of multicomponent crystal formed in this research was likely the salt-type crystal according to the pKa rules [13,23].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…1. the changes in the crystal lattice that occur due to the solid-state interaction between trimethoprim and mandelic acid molecules [13]. The type of multicomponent crystal formed in this research was likely the salt-type crystal according to the pKa rules [13,23].…”
Section: Resultsmentioning
confidence: 72%
“…Previous studies related to the formation of multicomponent crystals of trimethoprim have been investigated, including the formation of trimethoprim-sulfamethoxazole [10], trimethoprim-citric acid [11], and trimethoprim-maleic acid [12]. Our previous study also showed an improvement in trimethoprim solubility using mandelic acid as the co-former by solvent drop grinding method, which increased about 2.73 times [13].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…When MA was incorporated into (AS-30CAR-MA) films, the new diffracted peaks were observed at 2θ values of 9.5° and 28.6° and these diffracted peaks confirmed the presence of MA in the film [34]. With the increasing amount of MA, it was observed that the peak intensity at 2θ of 9.5° and 28.6° was slightly increased while the intensity of the peak at 2θ of 20.2° was decreased.…”
Section: Xrdmentioning
confidence: 69%